Can Changes in the Cost of Carry Explain the Dynamics of Corporate “Cash” Holdings? - Azar, José A.; Kagy, Jean-François; Schmalz, Martin C. (Review of Financial Studies, 2016)
Firms until recently were effectively constrained to hold liquid assets in non-interest-bearing accounts. As a result, the cost of capital of firms’ liquid-assets portfolios exceeded the return, especially when the risk-free interest rate was high. The spread between cost and return is the cost of carry. Changes in the cost of carry explain the dynamics of corporate “cash” holdings both in the United States and abroad, and the level of cost of carry explains the level of liquid-asset holdings across countries. We conclude that current US corporate cash holdings are not abnormal in a historical or international comparison. Received February 17, 2015; accepted October 1, 2015 by Editor David Denis.